1994
DOI: 10.1128/mcb.14.2.970-981.1994
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Histone Amino Termini in Facilitated Binding of a Transcription Factor, GAL4-AH, to Nucleosome Cores

Abstract: Facilitated, "cooperative" binding of GAL4-AH to nucleosomal DNA occurred in response to inhibition from the core histone amino termini. The binding of GAL4-AH (which contains the DNA-binding and dimerization domains of GAL4) to nucleosome cores containing multiple binding sites initiated at the end of a nucleosome core and proceeded in a cooperative manner until all sites were occupied. However, following tryptic removal of the core histone amino termini, GAL4-AH binding appeared to be noncooperative, similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Both removal and acetylation of the tails are thought to “loosen” the histone−DNA contacts due to the removal of positive charge in the vicinity of nucleosomal DNA. This is in line with studies in which either acetylation or removal of the tail domains has been coupled to increased transcription factor access ( ).…”
supporting
confidence: 90%
“…Both removal and acetylation of the tails are thought to “loosen” the histone−DNA contacts due to the removal of positive charge in the vicinity of nucleosomal DNA. This is in line with studies in which either acetylation or removal of the tail domains has been coupled to increased transcription factor access ( ).…”
supporting
confidence: 90%
“…Although we found clear instances of sites independently pioneered by either FOXA1 or HNF4A, not all sites containing multiple motifs were pioneered in K562 cells, which comports with studies showing that the sequence context in which motifs occur also plays an important role in determining whether sites will be pioneered or not. GAL4’s ability to bind nucleosomal DNA templates depends both on the number of copies of its motif ( Taylor et al, 1991 ) and the positioning of the motif in the nucleosome ( Vettese-Dadey et al, 1994 ). Precise nucleosome positioning also dictates TP53 and OCT4 pioneering behavior ( Yu and Buck, 2019 ; Huertas et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that binding of transcription factors to nucleosomal DNA is enhanced by acetylation. This assumption is based on the demonstration that hyperacetylation induces subtle alterations in nucleosomal structure which may increase the accessibility to transcription factors (13)(14)(15)(16). Nevertheless, Hager and colleagues reported that butyrate treatment inhibited glucocorticoid hormone-dependent formation of a nuclease hypersensitive site and blocked transcriptional induction of the mouse mammary tumor virus (MMTV) LTR (69).…”
Section: Discussionmentioning
confidence: 99%
“…The role of nucleosomes in regulating transcriptional activity is supported by histone acetylation experiments. Hyperacetylation of core histones has been shown to enhance binding of some transcription factors to nucleosomes (13)(14)(15)(16). One possible mechanism is that the histone basic N-terminal domains interact with nucleosomal DNA and prevent binding of transcription factors.…”
mentioning
confidence: 99%